2014
DOI: 10.5539/ass.v10n18p232
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Educators in the Context of Education Reform and Unrest: A Study of Southern Border Provinces in Thailand

Abstract: This qualitative study aimed to identify challenges of educators faced with education reform and violent unrest that has taken place in five Southern provinces of Thailand, as well as leadership characteristics that emerged in this context. Participants were 21 educators from primary schools in Pattani, Yala, Narathiwat, Songkhla and Satun provinces. A purposeful selection was employed for participant recruitment of the study. Data collection methods were semi-structured interviews and related official documen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 13 publications
(7 reference statements)
0
16
0
Order By: Relevance
“…Schwartz (2015) argued that this context was appropriate in that as a consequence of the collapse of the Somali state during a period of more than 26 years of continuous internal conflict, the vast majority of Somali educational institutions are privately-run (Abdi, 1998;Abdinoor, 2008). Responding to the case through this lens had an added benefit of allowing cogent reference to previous research on educational leadership in Southern Thailand, a region which has also suffered from an almost six-decades long Islamic insurgency that has also targeted secular educational institutions for attack (Brooks, 2015;Liow, 2010;Maxcy, Sungtong, & Nguyen, 2010;Nitjarunkul, Suntong, & Placier, 2014;Othman & Wanlabeh, 2012). Schwartz (2015) asserted that this was particularly important in that no research that directly addresses educational leadership in the Somali context could be found that could be applied to the case outlined by Aden (2015).…”
Section: Responsementioning
confidence: 99%
See 4 more Smart Citations
“…Schwartz (2015) argued that this context was appropriate in that as a consequence of the collapse of the Somali state during a period of more than 26 years of continuous internal conflict, the vast majority of Somali educational institutions are privately-run (Abdi, 1998;Abdinoor, 2008). Responding to the case through this lens had an added benefit of allowing cogent reference to previous research on educational leadership in Southern Thailand, a region which has also suffered from an almost six-decades long Islamic insurgency that has also targeted secular educational institutions for attack (Brooks, 2015;Liow, 2010;Maxcy, Sungtong, & Nguyen, 2010;Nitjarunkul, Suntong, & Placier, 2014;Othman & Wanlabeh, 2012). Schwartz (2015) asserted that this was particularly important in that no research that directly addresses educational leadership in the Somali context could be found that could be applied to the case outlined by Aden (2015).…”
Section: Responsementioning
confidence: 99%
“…The authors suggest that Somali universities should also heed the advice of Nitjarunkul, Suntong, and Placier (2014) and provide preparation for the unique challenges of educational leadership in the context of armed conflict. Likewise, as Carr-Hill (2015) documented, the irrelevance of the curriculum of formal schools to the nomadic pastoralists who compose 65 percent of the Somali population could be addressed by following Nitjarunkul, Suntong, and Placier's (2014) advice to localize instructional methodology.…”
Section: International Journal Of Educationmentioning
confidence: 99%
See 3 more Smart Citations